Isidori Hispalensis versus, cura et studio José Mª Sánchez Martín, Corpus Christianorum SL 113 A, Turnhout: Brepols, 2000, 274 pp., ISBN: 2-503-01133-0 (Minerva, 2019)
Review: Isidori Hispalensis versus, cura et studio José Mª Sánchez Martín, Corpus Christianorum SL 113 A, Turnhout: Brepols, 2000, 274 pp., ISBN: 2-503-01133-0